الخطاب المقاصدي عند المالكية بين أبعاده التنظيرية ومآلته التنزيلية القيم الأخلاقية أنموذجا - نورالدين لبصير (Université de M'sila, 2019)
الملخص: نروم من خلال هذه الدراسة مقاربة تمظهرات خطاب المقاصد الأخلاقية في الفقه المالكي بكل أبعاده الابستيمولوجية،والمعرفية ،والتي يتقاطع من خلالها الإشكال المنهجي الذي يؤصل للقيم الأخلاقية مع الإشكالات التطبيقية،وتنزيلاتها المقاصدية المختلفة،ومحاولة بناء التأسيس المفاهيمي لمقاصد الأخلاق. الكلمات المفتاحية:الخطاب الفقه؛ المالكية؛ المقاصد؛ الأخلاق؛التنظير؛ التنزيل-المفاهيم؛ القيم. Résumé: Il reste l'objectif principal de cette étude est d'essayer de rapprocher la présentation de discours la lettre des buts moraux dans la jurisprudence malki dans toutes ses dimensions éépistémologie et cognitif qui croise a travers les problèmes méthodologiques lesquels sont enracines les valeurs éthiques avec la problématique appliquée, et essayer de construire la base des concepts des fins de la ,oralité. Maliki jurisprudence in all its dimensions Epistemological, and cognitive, through which the methodological problem that establishes ethical values intersects With the practical problems, and its various distributions, and the attempt to build the conceptual foundation of the purposes of morality. Watch is the approach to morphology The moral purposes in the Maliki jurisprudence Based on this problem; we want through this study ;the approach of massed ethics in the maliik jurisprudence between the theoretical and applied dimension; it is impossible to talk abut the theoretical aspect without translating it into application; otherwise the attempt is turned into a random mzss;when the two sides had an integrative relationship we tried the test of ethics in the books Maliki jurisprudence; and the transition form theoretical perception to the spaciousness of application. And the need for ethics after the founding of the theoretical p to the practical side, especially with regard to the purposes. The Maalikis understood the importance of in the life of a Muslim jurisprudence; therefore; jurisprudence has great place. All this promoted the researcher to extract these ethical purposes as ode that combines theory and application In the absence of jurisprudence purposes in or daily life ;especially in the era of moral decay and the overthrow of concepts ; we tooth on the evangelists to uphold the moral role in all walks of life. Maliki jurisprudence in all its dimensions Epistemological, and cognitive, through which the methodological problem that establishes ethical values intersects With the practical problems, and its various distributions, and the attempt to build the conceptual foundation of the purposes of morality. Watch is the approach to morphology The moral purposes in the Maliki jurisprudence Based on this problem; we want through this study ;the approach of massed ethics in the maliik jurisprudence between the theoretical and applied dimension; it is impossible to talk abut the theoretical aspect without translating it into application; otherwise the attempt is turned into a random mzss;when the two sides had an integrative relationship we tried the test of ethics in the books Maliki jurisprudence; and the transition form theoretical perception to the spaciousness of application. And the need for ethics after the founding of the theoretical p to the practical side, especially with regard to the purposes. The Maalikis understood the importance of in the life of a Muslim jurisprudence; therefore; jurisprudence has great place. All this promoted the researcher to extract these ethical purposes as ode that combines theory and application In the absence of jurisprudence purposes in or daily life ;especially in the era of moral decay and the overthrow of concepts ; we tooth on the evangelists to uphold the moral role in all walks of life.
Keywords: Keywords: discours- Jurisprudence- Maalikis- Maqassed- Ethics- Endoscopy- Concepts- Values. ; الكلمات المفتاحية:الخطاب الفقه؛ المالكية؛ المقاصد؛ الأخلاق؛التنظير؛ التنزيل-المفاهيم؛ القيم.